2004
DOI: 10.1002/maco.200303748
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the mode of introduction of a reactive element on the high temperature oxidation behavior of an alumina‐forming alloy. Part I: Isothermal oxidation tests

Abstract: Different modes of introduction of yttrium have been tested with regard to the influence on the high temperature oxidation behavior of a FeCral alloy. Y2O3 sol‐gel coatings, Y2O3 metal‐organic chemical vapor deposition (MOCVD) coatings, implanted yttrium ions and yttrium as alloying element (0.1 wt.%) in the same Fe‐20Cr‐5Al alloy were oxidized at 1100°C in air under atmospheric pressure. Whatever the mode of introduction of the reactive element, the oxidation rates were not decreased compared to the oxidation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 57 publications
(23 reference statements)
0
12
0
Order By: Relevance
“…The same effect was observed already in a previous study which used Y + ion implantation or sol-gel or MOCVD coatings as the introduction route for yttrium in Fe-Cr-Al alloys. [73][74][75] The aluminized diffusion coatings seem to be efficient in producing alumina scales. Even in the case of spallation, the Al reservoir appears high enough to guarantee growth of an alumina scale.…”
Section: Discussionmentioning
confidence: 98%
“…The same effect was observed already in a previous study which used Y + ion implantation or sol-gel or MOCVD coatings as the introduction route for yttrium in Fe-Cr-Al alloys. [73][74][75] The aluminized diffusion coatings seem to be efficient in producing alumina scales. Even in the case of spallation, the Al reservoir appears high enough to guarantee growth of an alumina scale.…”
Section: Discussionmentioning
confidence: 98%
“…This is particularly true for reactive-element addition, whose effect on the high-temperature corrosion of alumina-forming materials was largely studied [16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…The introduction methods and the characterisation of the starting materials were described in Part I of this work [1].…”
Section: Methodsmentioning
confidence: 99%
“…No yttrium containing phases could be detected even from the beginning of the oxidation experiments. But it was previously observed that no crystallised phases were formed during the sol-gel process [1]. aAl 2 O 3 grew after 1 h and developed until the end of the oxi- For implanted specimens, the in situ XRD results are reported on Fig.…”
Section: In Situ High Temperature X-ray Diffraction Studiesmentioning
confidence: 99%
See 1 more Smart Citation